Mechanism and threshold of environmental stressors on seagrass in high-turbidity estuary: case of Zostera japonica in Yellow River Estuary, China - Yi, Yujun; Zhao, Fanxuan; Hou, Chuanying; Zhang, Chengxiang; Tang, Caihong (Frontiers in Marine Science, 2024)
Zostera japonica (Z. japonica), the most widely distributed seagrass species in temperate estuaries, has experienced a dramatic decline of nearly 75% over the past decade. While previous research has investigated the adaptation of seagrass individuals and populations to single stress factors, the molecular mechanisms underlying the interaction of multiple stressors remain poorly understood. This study conducted laboratory experiments to examine the response of Z. japonica at different life stages to environmental pressures, specifically salinity and turbidity, as indicated by changes in free amino acids (FAAs). The results demonstrate that Z. japonica exhibits stronger adaptability to high salinity environments but displays weaker adaptability to freshwater conditions. Through single stress experiments, the salinity and turbidity thresholds for FAA homeostatic disturbance in Z. japonica were determined at seedling, juvenile, and mature stages. As Z. japonica matures, its metabolic pathways expand and diversify, allowing the regulation of key FAAs to enhance stress resistance. Turbidity stress exerts a more pronounced negative impact on the cellular homeostasis of Z. japonica compared to salinity stress, and when turbidity levels exceed 150 NTU, they significantly intensify the negative effects of salinity stress on the seagrass. Furthermore, under strong salinity-turbidity interactions, the concentration of key FAAs generally decreases by 20-30%, indicating inhibition of growth and development in Z. japonica. These findings have important implications for the conservation of intertidal seagrass beds and estuarine ecosystems in the face of multiple human activities and environmental stressors. The study provides valuable insights into the molecular mechanisms underlying Z. japonica's adaptations to salinity and turbidity stress, contributing to the development of targeted strategies to mitigate the impacts of environmental pressures on seagrass populations and promote the resilience of these critical marine ecosystems.